"Treat and repair" strategy for shunt lesions: a critical review. (1st April 2020) - Arvind, Balaji; Relan, Jay; Kothari, Shyam S.
Abstract : The issue of operability in patients with shunt lesions and raised pulmonary vascular resistance is contentious. Several reports suggest that patients traditionally considered inoperable may be operated after treatment with targeted drug therapy for pulmonary arterial hypertension. We reviewed all the published literature of "treat and repair" approach to gain more insights into the utility of this approach. A critical appraisal of the published literature suggests that this approach is less established for patients with post tricuspid shunts, and for patients with pre‐tricuspid shunts with modestly elevated indexed pulmonary vascular resistance (possibly greater than 11 WU.m 2 ). Targeted drug therapy may be able to extend the therapeutic window in carefully selected patients, but its use as a routine in this setting seems unwarranted.